Equality Of Parenting Accepted By Parent Of Preschool Children Invillage Sridadi Rembang - Pranata, Vicky Riyan; Putri, Estetika; Indanah, Indanah; Karyati, Sri (Prosiding University Research Colloquium, 2021)
Background: In the 80's, parents in educating their children, must experience differences in today's digital era. Parenting patterns of parents who initially experienced differences from other parents, who only applied authoritarian, permissive, and democratic parenting styles have experienced success in educating children, but in the digital era, these three parenting styles will not succeed, if they do not do synchronization according to the time of the situation and conditions in terms of parenting. Objective: To find out the similarity of parenting received by parents in preschool children in Sridadi Village, Rembang in 2021. Methods: This study uses quantitative research methods with correlation research. Cross sectional approach method. The sample collection technique used is the Proportionate Stratified Random Sampling method, the population in the village is 163 and the sample is 116 respondents. Bivariate analysis using Spearman Rho test and the instrument used is a questionnaire sheet. Results: The results showed that out of 116 respondents who had fairly good parenting styles, 93 respondents (80.2%) and 23 respondents (19.8%) had poor parenting styles. Conclusion: The similarity of parenting received by parents from 116 respondents to preschool age children mostly do good parenting with a frequency of 93 respondents (80.2%).